Health Problems for the Elderly and Their Influence on Their Psychological Health (Journal Of Educational and Psychological Researches, 2022)
The current research seeks to identify the most important humanitarian issues of a sacred and very important group in all the heavenly religions and human societies, namely the elderly, to identify their significant problems and health problems, and What are the effects of these problems on their mental health and which is the ultimate goal of human resources in All parts of the world? The study relied on what is available from the sources in the literature starting from the messages of heaven and the Islamic religion followed with humanitarian, social, legal and psychological postulates. The research included four systematic chapters included the definition research and identification of the problem, importance, objectives and terminology, then the literature and theoretical frameworks for the elderly and their health problems and impact on mental health from a religious perspective, in the Koran, Sunnah, and the most important psychological theories that explained their situation, especially the elderly in Iraqi society, and the most important laws that started for them. The definition of the concept of mental health for the elderly and the effects of health problems on them, and clarify some of the procedures to assist in reducing its intensity preventively and medically. The research came out with a number of conclusions, recommendations and suggestions.